Uncovering Partnership among Village Stakeholders in Village Governance: An Evidence from East Java, Indonesia - Said, Abdullah (International Journal of Criminology and Sociology, 2022)
This study uncovers the partnership interactions that occur in village government in East Java and aims to determine the partnership, described and explained in the form of a quadrant-type of analysis through two dimensions of Government and Non-partnership. The existence of two institutions (village government and BPD) that carried out village governance requires a robust partnership and mutual interactions among both in the implementation of their activities, the pattern of partnership relations itself has become a trend in public administration and good governance practices, where partnerships are considered capable of increasing the effectiveness of governance in the provision of public services. The data analysis used in this research is descriptive quantitative by measuring the mean of two dimensions, so that it can describe the quadrant that explains the partnership relationship between the two institutions. The results of this analysis indicate that the partnership relationship that occurs occupies the partnership quadrant, meaning that there is a high alliance between the two institutions.